Reasons of Absenteeism among Undergraduate Medical Students: A Review - Sharmin, Tanima; Azim, Ehsamul; Choudhury, Shamima; Kamrun, Sayma (Anwer Khan Modern Medical College Journal, 2017)
Absenteeism refers to the frequent absence from classes without any good reason. In spite of compulsory attendance rule, individual students, parents, institute and society suffer when students do not attend classes in medical college on regular basis. Student absenteeism is a concern in higher education especially medical education. Student's absenteeism results in inadequate learning and poor academic performance. Despite the strict rules, absenteeism is an on-going problem in many universities and a phenomenon that is also on the rise in universities worldwide. There is extensive literature on the link between absenteeism and lack of subject matter interest, poor teaching strategies, unfavorable learning environment,excessive socialization among students, part-time jobs, ill health, sleeplessness and poor relations with lecturers. In addition, accessibility of lecture content in the form of online slides, videos and audios has their own contribution to absenteeism. Early detection and prevention might prevent unwanted consequences of absenteeism on medical students' academic performance.Medical colleges should pay more attention and take immediate measures on those who starting to absent from classes because they might need support from them. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 60-66